2019
DOI: 10.1021/acs.jpclett.9b01855
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of the Static Picture of Defect Energetics in Halide Perovskites: The Case of the Br Vacancy in CsPbBr3

Abstract: We consider the Br vacancy in CsPbBr3 as a prototype for the impact of structural dynamics on defect energetics in halide perovskites (HaPs). Using first-principles molecular dynamics based on density functional theory, we find that the static picture of defect energetics breaks down; the energy of the VBr level is found to be intrinsically dynamic, oscillating by as much as 1 eV on the ps time scale at room temperature. These significant energy fluctuations are correlated with the distance between the neighbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 113 publications
3
56
0
Order By: Relevance
“…Therefore the proposition that defects may contribute to the observed dielectric response does not contradict the excellent PL efficiency of CsPbBr 3 NCs. The link between the dipolar relaxation and lattice defects in CsPbBr 3 is supported by molecular dynamics simulations, which have shown that the positions of lattice ions at halide vacancies fluctuate on a similar time scale (5 ps) 79 as our measured relaxation ( τ = 32 ps) (by comparison, relaxation due to Cs + motion occurs on a time scale of around 100 fs 15 ). The charge density around a defect depends strongly on the positions of neighboring ions, such that these fluctuations may induce a dipole which can respond to an electromagnetic field, as required for configurational tunneling.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore the proposition that defects may contribute to the observed dielectric response does not contradict the excellent PL efficiency of CsPbBr 3 NCs. The link between the dipolar relaxation and lattice defects in CsPbBr 3 is supported by molecular dynamics simulations, which have shown that the positions of lattice ions at halide vacancies fluctuate on a similar time scale (5 ps) 79 as our measured relaxation ( τ = 32 ps) (by comparison, relaxation due to Cs + motion occurs on a time scale of around 100 fs 15 ). The charge density around a defect depends strongly on the positions of neighboring ions, such that these fluctuations may induce a dipole which can respond to an electromagnetic field, as required for configurational tunneling.…”
Section: Discussionsupporting
confidence: 71%
“…[50][51][52] Moreover, these fluctuations have been shown to greatly affect the defect energy landscape. 53 Clearly, the static, relaxed structure can only represent an average picture. Because the static FA +containing structure is already greatly distorted even in the absence of dynamic effects, much more so than the Cs + -containing one, it is reasonable to assume that these differences carry over to the dynamic, room temperature systems.…”
Section: Results: Origin Of Self-healing In the Bulkmentioning
confidence: 99%
“…[70][71][72] Moreover, these fluctuations may affect the defect energy landscape. 73 Clearly, the static, relaxed structure can only represent an average picture.…”
Section: Br I + : Relation Between Geometry and Stabilitymentioning
confidence: 99%
“…Low temperature solution processing with very fast crystallization under the condition of kinetic competition between many processes should lead to high concentrations of crystal defects. However, somehow it is not a severe problem for device efficiency [2–5] . Here it is important to realize that not every defect leads to NR recombination, and even if some do, their efficiency can vary enormously.…”
Section: Defects Are Importantmentioning
confidence: 99%